UK specification for ground investigation (ICE, 2012)
Intended for general application to ground investigation work this specification includes associated schedules and a bill of quantities. The bill of quantities is presented as an introduction and a comprehensive list of work items, which relates closely to the specification items.
At foot of title: Highways Agency, Network Rail.
Keywords: Building sites -- Great Britain -- Planning.; elektronické knihy; electronic books